2016
DOI: 10.1007/s00429-016-1223-z
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia and cerebellar interconnectivity within the human thalamus

Abstract: Basal ganglia and the cerebellum are part of a densely interconnected network. While both subcortical structures process information in basically segregated loops that primarily interact in the neocortex, direct subcortical interaction has been recently confirmed by neuroanatomical studies using viral transneuronal tracers in non-human primate brains. The thalamus is thought to be the main relay station of both projection systems. Yet, our understanding of subcortical basal ganglia and cerebellar interconnecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 91 publications
(140 reference statements)
2
35
0
2
Order By: Relevance
“…Conversely, we (Pelzer et al 2017) demonstrated a decreasing anterior-to-posterior gradient for pallido-thalamic connections in: (1) the ventral-anterior thalamus; (2) the intralaminar nuclei; and (3) midline regions. Moreover, we presented evidence for a decreasing posterior-to-anterior gradient for dentato-thalamic projections predominantly in: (1) the ventral-lateral and posterior nucleus; (2) dorsal parts of the intralaminar nuclei and the subparafascicular nucleus, and (3) the medioventral and lateral mediodorsal nucleus.…”
Section: Studies In the Human Speciesmentioning
confidence: 55%
See 1 more Smart Citation
“…Conversely, we (Pelzer et al 2017) demonstrated a decreasing anterior-to-posterior gradient for pallido-thalamic connections in: (1) the ventral-anterior thalamus; (2) the intralaminar nuclei; and (3) midline regions. Moreover, we presented evidence for a decreasing posterior-to-anterior gradient for dentato-thalamic projections predominantly in: (1) the ventral-lateral and posterior nucleus; (2) dorsal parts of the intralaminar nuclei and the subparafascicular nucleus, and (3) the medioventral and lateral mediodorsal nucleus.…”
Section: Studies In the Human Speciesmentioning
confidence: 55%
“…Briefly, in the analysis of connectivity distributions, two different approaches can be taken: (1) tractography-based parcellation as recently shown for the thalamic connections with the cerebellum and basal ganglia in (Lambert et al 2016) or (2) characterization of projections and atlas-based assessment of connectivity fingerprints per thalamic regions as recently demonstrated by our group (Pelzer et al 2017).…”
Section: Studies In the Human Speciesmentioning
confidence: 99%
“…The BG-thalamus-cerebellum network might play an important role in procedural knowledge and learning, as evident during the DNS core stabilization exercise. It is plausible that the thalamic ventral lateral nucleus modulates core muscle activation and the learning process while interacting with cortical (SMA, PMC, anterior cingulate cortex) and subcortical targets (BG and cerebellum) [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that report on connections of the dentate with specific thalamic nuclei in cats, monkeys, and humans using tract tracers and diffusion MRI (Bernard et al, 2013;Holsapple et al, 1991;Jimenez-Castellanos and Reinoso-Suarez, 1985;Pelzer et al, 2017). However, collective data regarding the dento-thalamic connections is rather sparse.…”
Section: Discussionmentioning
confidence: 99%